Immunogenic cell death-related risk signature predicts prognosis and characterizes the tumour microenvironment in lower-grade glioma - Cai, Jiayang; Hu, Yuanyuan; Ye, Zhang; Ye, Liguo; Gao, Lun; Wang, Yixuan; sun, Qian; Tong, Shiao; Yang, Ji’an; Chen, Qianxue (Frontiers in Immunology, 2022)
Lower-grade glioma (LGG) is the common malignant primary tumor in the central nervous system, which most patients will eventually develop into highly aggressive gliomas despite comprehensive traditional treatment. And the tumor molecular subtypes and prognostic biomarkers play a crucial role in LGG diagnosis and treatment. Therefore, the identification of novel biomarkers in LGG patients is crucial for predicting the prognosis of glioma. Immunogenic cell death (ICD) was defined as a regulated cell death that is sufficient to activate the adaptive immune response of immunocompetent hosts. The combination of ICD and immunotherapy might exert a greater and more lasting anti-tumor effect in gliomas. In our study, we explored the expression, function, and genetic alterations of 34 ICD-related genes. Based on 12 ICD-related genes, we constructed and validated an ICD-related risk signature via the least absolute shrinkage and selection operator (LASSO) cox regression analysis. All the information was obtained from the public database including The Cancer Genome Atlas (TCGA), Genotype-Tissue Expression (GTEx), and the Chinese Glioma Genome Atlas (CGGA) databases. Our results found that ICD-high risk groups have a poor prognostic and might be more sensitive to immune checkpoint blockade (ICB) immunotherapy. In addition, ICD-high risk groups were associated with 1p19q non-codeletion, higher WHO grade, IDH wild type, and immunosuppressive tumor microenvironment. We verified the prognostic value of 12 ICD-related genes in TCGA and CGGA databases. And Immunohistochemistry was used to verify the expression of several ICD-related genes at the protein level. Our study provides a novel and comprehensive perspective to elucidate the underlying mechanisms of LGG prognosis and provides direction for future individualized cancer immunotherapy.